2019
DOI: 10.1111/bju.14642
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of circulating tumour cells predict time to castration resistance in metastatic castration‐sensitive prostate cancer

Abstract: Objectives To identify biomarkers that predict the response to standard androgen deprivation therapy (ADT) of patients newly diagnosed with metastatic castration‐sensitive prostate cancer (CSPC) in order to improve therapeutic decision‐making, and to investigate whether the characterization of baseline circulating tumour cells (CTCs) would predict the effective period of standard ADT. Materials and Methods The study included 108 patients newly diagnosed with high‐volume metastatic CSPC. Enumeration and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…A recent in vivo animal study demonstrated that epithelial CTCs with restricted mesenchymal transition are a major source of metastases in BCa (Liu et al, 2019). Still more studies support that mesenchymal CTCs are more important to predict patients' survival outcomes (Pastushenko & Blanpain, 2019;Hou, Guo & Lyu, 2019;Yang et al, 2019). But evidences suggest that poor prognosis of patients with more mesenchymal CTCs might be due to the increased chemoresistance rather than metastasis potential (Fischer et al, 2015;Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vivo animal study demonstrated that epithelial CTCs with restricted mesenchymal transition are a major source of metastases in BCa (Liu et al, 2019). Still more studies support that mesenchymal CTCs are more important to predict patients' survival outcomes (Pastushenko & Blanpain, 2019;Hou, Guo & Lyu, 2019;Yang et al, 2019). But evidences suggest that poor prognosis of patients with more mesenchymal CTCs might be due to the increased chemoresistance rather than metastasis potential (Fischer et al, 2015;Zheng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Further, in a study of 108 patients with newly diagnosed castrate-sensitive PCa, expression of mesenchymal markers in CTCs at baseline was found to be an independent prognostic factor that was predictive of time to progression to CRPC following standard ADT. Patients who had mesenchymal CTCs at baseline showed a significantly shorter time to progression to CRPC than patients without CTCs or patients whose CTCs were negative for mesenchymal markers [21]. Several studies show that E-cadherin suppresses invasion and metastasis in vitro, and consistent with these findings, E-cadherin staining in tumor tissue correlates with longer overall survival [84].…”
Section: Clinical Relevance Of Emt Markers In Pcamentioning
confidence: 81%
“…MET, on the other hand, is thought to aid CTCs after leaving the vascular system to be able to settle in other tissues and form new tumors [18,19] (Figure 1). us, CTC numbers have been recognized as a marker of metastatic disease, and importantly, EMT markers have been screened for in patient CTCs including those of 54 patients with PCa, 53% of these patients had advanced metastatic disease and intermittent epithelial-to-mesenchymal phenotype of CTCs correlated with metastasis in these patients, while another study found that the mesenchymal CTC phenotype correlated with increased rates of progression to CRPC in a cohort of 108 PCa patients recruited with high volume metastatic disease at hormone-sensitive disease stage and longitudinally followed during the study [20][21][22]. Metastatic spread of cancer is thought to involve different stages (Figure 1(a)) in which cancer cells (i) lose cell-cell tight junctions and detach from the primary site/organ, (ii) penetrate the basal lamina and enter nearby tissue, (iii) evade programmed cell death normally induced by loss of substrate adhesion (anoikis), (iv) breach blood or lymphatic vessels and migrate to other sites via blood/lymphatic circulation, (v) leave the bloodstream or lymphatic vessels at distant organs, (vi) form a micrometastatic core, and finally (vii) adjust and reprogram the surrounding stroma to form detectable macrometastases [23].…”
Section: Circulating Tumor Cells and Emt In Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…In metastatic castration-sensitive PCa, EMT CTCs at baseline predicted the effective time of standard ADT. 43 Our study focused on localized PCa patients, suggesting the number of biophenotypic CTCs was closely related to a series of clinical variables (Table 3). In the logistic regression analysis on OC, biophenotypic CTCs and clinical stage were the only two significant factors, with similar hazard ratio, which means this mixed subtype CTCs were as important as clinical stage.…”
Section: Discussionmentioning
confidence: 98%